Application of elevation geomorphologic classification for checking the accuracy of digital elevation model - Kumetaitienė, Aušra (Geodesy and Cartography, 2012)
The article deals with the geomorphologic method of classification of the elevation, applying a special overlay of the first and second rate derivative of the elevation. So far in the tests there have been taken into account one or two characteristics for classification. The technique presented suggests the method of joining together some surface characteristics and by summarising as well as associating them together to make one rugged surface of the elevation to be able to reflect the most precisely and comprehensively the elevation changes in the spherical image and it should serve best for selecting the elevation model and parameters of modelling. The errors of the elevation models obtained by means of different modelling techniques have been evaluated. The results revealed that the elevation models errors depend on geomorphologic characteristics. These errors have been calculated by means of different methods. The efficiency of the method has been evaluated calculating the elevation model for each. The possibilities to reduce the standard deviations of the elevation model have been evaluated by selecting the parameters of the elevation modelling. First published online: 03 Aug 2012